Respuesta :

...........................................................................................................................................................................................................................................................................................................................................................................

Ver imagen sreekpuk

[tex]-6h^{2}+5h+2=0\\h^{2} -\frac{5}{6} h-\frac{1}{3} =0\\h^{2} -\frac{5}{6} h+(\frac{5}{12} )^{2} -(\frac{5}{12} )^{2}-\frac{1}{3} =0\\(h-\frac{5}{12} )^{2} =\frac{1}{3} +(\frac{5}{12} )^{2}\\(h-\frac{5}{12} )^{2} =\frac{73}{144} \\[/tex]

[tex]h-\frac{5}{12} = \sqrt{\frac{73}{144}} \\h=\sqrt{\frac{73}{144}} +\frac{5}{12}[/tex]

or

[tex]h-\frac{5}{12} = -\sqrt{\frac{73}{144}} \\h=-\sqrt{\frac{73}{144}} +\frac{5}{12}[/tex]